2003
DOI: 10.1021/nl034008t
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir−Blodgett Film Deposition of Metallic Nanoparticles and Their Application to Electronic Memory Structures

Abstract: The Langmuir−Blodgett deposition of organically passivated gold nanoparticles is reported. A monolayer of these particles has been incorporated into a metal−insulator−semiconductor (MIS) structure. The MIS device exhibits a hysteresis in its capacitance versus voltage characteristic, the magnitude of which is dependent on the voltage sweep conditions. Charge storage in the layer of nanoparticles is thought to be responsible for this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
194
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(200 citation statements)
references
References 14 publications
1
194
1
4
Order By: Relevance
“…The organically capped nanoparticles used in this work ͑Q-Au͒ were prepared using Schlenk line techniques. 13,14 The devices investigated in this work were all prepared in a class 1000 microelectronics clean room. Substrates were glass microscope slides.…”
Section: Methodsmentioning
confidence: 99%
“…The organically capped nanoparticles used in this work ͑Q-Au͒ were prepared using Schlenk line techniques. 13,14 The devices investigated in this work were all prepared in a class 1000 microelectronics clean room. Substrates were glass microscope slides.…”
Section: Methodsmentioning
confidence: 99%
“…5,18 In the first type of device, switching mechanisms are explicitly explained by the theory that electron charge transfer from conjugate molecules or polymers (donor) to NPs (acceptor) results in the "ON" state and the reverse transfer of electrons from acceptor to donor by a built-in negative electric field in turn leads to the "OFF" state. This type of device shows a…”
Section: Introductionmentioning
confidence: 99%
“…In the previous paper it has shown that the resistive switching will occur through the polymer capped nanostructure silver oxide embedded in a planer diode with two gold electrodes [1]. There are lots of reports showing different mechanisms for resistive switching observation [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%